PENGARUH METODE COOPERATIVE LEARNING DENGAN TIPE EXAMPLE NON EXAMPLE DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS V SD NEGERI 7 PSEKSU - Nofarita Asyiah (Prodi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan UIN Sulthan Thaha Saifuddin Jambi, 2025)
The purpose of this study aims to determine the effect of the application of the Cooperative Learning method Example non Example type on the learning outcomes of fifth-grade students of SD Negeri 7 Pseksu with the research subjects being fifth-grade elementary school students in the 2022/2023 academic year. With the existence of classroom action research with several cycles, namely cycle I and cycle II with research steps in the form of planning, implementation, observation and also reflection in each cycle. The study uses descriptive analysis techniques that describe the process of each cycle carried out with corrective action steps. Before the corrective action was implemented, student learning outcomes had an average of 58. While in cycle I there was an average increase of 72.4. Actions were carried out again in cycle II and found an average increase of 83.2 with a fairly good predicate. Based on these results, it can be seen that there is an influence between the Cooperative Learning method and the Example non Example technique on the learning outcomes of fifth-grade students of SD Negeri 7 Pseksu in the Indonesian Language subject with the material responding to events.